PENGARUH KONTROL KELUARGA TERHADAP MANAJEMEN LABA - Ancilla Sheila Margono; Yulia Ivana Tanujaya; Athalia Ariati Hidayat; Retno Yuliati (Jurnal Akuntansi, 2019)
The involvement of the family in the company can lead to conflict between the majority (family) and minority shareholders. This study aims to determine whether family control in companies listed on the Indonesia Stock Exchange (IDX) has a significant positive effect on earnings management. Earnings management in this research is measured using the Modified Jones Model. With a sample of 436 non-financial companies listed on the Stock Exchange in the period 2012-2016 and using the generalized least squares (GLS) regression method, the study found that family control had a significant positive effect on earnings management. This indicates that family control in companies listed on the Stock Exchange tends to do earnings management.Keywords: Family Control, Earnings Management, Modified Jones Model